Promoting Factors of Social Inclusion of Students With Special Educational Needs: Perspectives of Parents, Teachers, and Students - Lindner, Katharina-Theresa; Hassani, Sepideh; Schwab, Susanne; Gerdenitsch, Cornelia; Kopp-Sixt, Silvia; Holzinger, Andrea (Frontiers in Education, 2022)
The idea of inclusion in the sense of participating access to educational opportunities is widely acknowledged and implemented within the pedagogical discourse. Nevertheless, ensuring social participation of students with and without special education needs in learning situations continues to be challenging. The present study examines promoting and hindering factors for social inclusion with a focus on students with special educational needs. Therefore, semi-structured interviews regarding students’ (n = 12 students with SEN, 12 students without SEN), parents’ (n = 24), and teachers’ (n = 6 regular teachers, 6 special need teachers) perceptions of promoting educational characteristics that might influence students’ inclusion in everyday school life are analyzed through thematic analysis. The findings provide a wide range of pedagogical interventions that have the potential to promote inclusive education processes on educational, intrapersonal, and interpersonal levels as well as regarding different actors who are involved.